Bimaxillary Aneurismal Bone Cyst in Patient with End Stage Renal Disease and Hyperparathyroidism: A Rare Case Report and Review of the Literature - Sedigheh Bakhtiari; Mahin Bakhshi; Fatemeh Mashhadiabbas; Hasan Mir Mohammad Sadeghi; Zahra Elmi Rankohi; Somayeh Rahmani (Case Reports in Dentistry)
Aneurismal bone cyst (ABC) is a rare bony lesion occurring predominantly in long bones. Its jaws’ involvement is uncommon and the simultaneous involvement of both jaws is very rare. This report is about a 27-year-old female experiencing renal failure with ABC involving her maxilla and mandible. The progressive lesion was treated surgically and there was no recurrence after 18 months of follow-up.